Relationship between translanguaging strategy, communication and English academic performance among secondary school learners in ESL classroom in Kuala Terengganu - Abd Rahman, Siti Nadhirah; Razali, Nurfarah Hanna (Faculty of Educational Studies, Universiti Putra Malaysia, 2024)
In Malaysia, English serves as a second language for students expected to achieve B1/B2 proficiency by secondary school graduation. While students are fluent in Malay, Mandarin, or Tamil, English proficiency is essential. Translanguaging, which utilizes students' full linguistic repertoire, is a common instructional method, though it raises concerns about potentially hindering overall English proficiency and communication due to limited immersion. This proposed study aims to: (1) examine the translanguaging strategy, level of communication, and English academic performance among secondary school learners in ESL classroom in Kuala Terengganu; (2) examine the relationship between translanguaging strategy and communication among secondary school learners in ESL classroom in Kuala Terengganu; and (3) examine the relationship between translanguaging strategy and English academic performance among secondary school learners in ESL classroom in Kuala Terengganu. Despite evidence of translanguaging's benefits and drawbacks, no prior research has directly investigated these relationships. Utilizing a quantitative research design, questionnaires will be distributed to secondary students in a rural school setting. While the anticipated findings are expected to provide valuable insights into the relationship between translanguaging strategy, communication, and English performance, it is important to note that this is a proposed study, and the research has yet to be conducted.